Analisis perbandingan metode Hermeneutik dan Tafsīr bi al-Ra’yī dalam penafsiran al-Quran: Comparative analysis on Hermeneutic and Tafsir bi al-Ra’yī in Quranic exegesis - Zainal Abidin, Salman; Ibrahim, Mazlan (al-Irsyad: Journal of Islamic and Contemporary Issues, 2018)
Hermenutics, a method of interpreting the Qur’an, was first introduced by a controversial Muslim Scholar, Hasan Hanafi. His effort is followed by some other Muslim scholars such as Fazlur Rahmān, Naṣr Ḥāmid Abū Zayd and Muḥammad Arkoun. Apparently, Hermeneutics is similar to Tafsīr bi al-Ra’yī which employs pure reason and logic as the medium of interpreting the Qur’an. However, to a certain extent, Hermeneutics has significant differences from the concept of Tafsīr bi al-Ra’yī which encourages a large number of Muslim scholars to reject hermeneutics in understanding the Qur’an. Hence, this article is meant to epistemologically evaluate Hermeneutics in terms of its definition, history, development, scholars, and comparison with Tafsīr bi al-Ra’yī.